From organoids to bedside: advances in modeling, decoding and targeting of colorectal cancer: invited review - Betge, Johannes; Jackstadt, René-Filip (International journal of cancer, 2023)
Patient derived organoids closely resemble the biology of tissues and tumors. They are enabling ex vivo modeling of human diseases and dissecting key features of tumor biology like anatomical diversity or inter- and intra-tumoral heterogeneity. In the last years, organoids were established as models for drug discovery and explored to guide clinical decision making. In this review, we discuss the recent developments in organoid based research, elaborating on the developments in colorectal cancer as a prime example. We focus our review on the role of organoids to decode cancer cell dynamics and tumor microenvironmental complexity with the underlying bi-directional crosstalk. Additionally, advancements in the development of living biobanks, screening approaches, organoid based precision medicine and challenges of co-clinical trials are highlighted. We discuss ongoing efforts to overcome challenges that the field faces and indicate potential future directions.
Erstmals veröffentlicht: 19 September 2022
Gesehen am 17.06.2024